2018
DOI: 10.1080/19424280.2018.1538262
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged occupational standing: the impact of time and footwear

Abstract: Prolonged occupational standing is strongly related to musculoskeletal disorders. Despite being the main external load bearing interface between the floor and musculoskeletal system, and easy to manipulate, footwear is often ignored as an intervention for standing related disorders. This study aimed to record the effect of prolonged standing on the body and determine the impact of footwear material. Two pairs of surgical clogs were tested, varying only in material hardness. Participants (n=12) undertook 3 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Yes, my feet get a lot more arch shape to them when I take the weight off them and a resultant reduction of pressure in other regions. This is in agreement with previous walking and standing research [14,15,22,23] and suggests that for these work-based tasks lower plantar pressure was an important component for comfort. Medial midfoot pressure was increased by using a softer material in the heel/forefoot section or by having a harder material under the medial arch.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Yes, my feet get a lot more arch shape to them when I take the weight off them and a resultant reduction of pressure in other regions. This is in agreement with previous walking and standing research [14,15,22,23] and suggests that for these work-based tasks lower plantar pressure was an important component for comfort. Medial midfoot pressure was increased by using a softer material in the heel/forefoot section or by having a harder material under the medial arch.…”
supporting
confidence: 93%
“…The preference for harder arch materials in those with lower arched feet might be due to an increase in foot arch height that the material provides [ 28 ]. A softer arch material may enable contact with the arch in medium and high arched feet [ 29 ] and this contact may affect comfort [ 14 , 15 ]. However, we did not measure the actual response of the arch geometry and foot joints to the insoles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the nature of the work involved in each role was not explored in great detail, that is, how much time workers spent standing, walking or sitting in each role. Previous research has reported that an estimated 50% of the working population experience musculoskeletal disorders due to prolonged standing and that standing is implicated in lower back, lower limb and foot pain [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Safety footwear was also reported as being hot, heavy and providing poor ankle support. Many studies have explored the relationship between safety footwear and injuries with the majority focusing on; high cut lace up safety boots, military boots, gum boots, sports shoes [10] and surgical clogs [23]. These studies have identi ed many relationships, for example, gum boots are associated more with knee and heel pain while high cut lace up safety boots were associated with more leg and ankle pain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly 63.3% of participants worked in more than one role, highlighting the multifaceted nature of wine industry work. While this survey did not explore the nature of the work involved in each role, i.e., time spent standing, walking or sitting, previous research has reported that an estimated 50% of the working population experience musculoskeletal disorders due to prolonged standing and that standing is implicated in lower back, lower limb and foot pain [23,24].…”
Section: Job Rolementioning
confidence: 99%